Layers of epidemy: Present pasts during the first weeks of COVID‐19 in western Kenya. (27th July 2020) - Geissler, P. Wenzel; Prince, Ruth J.
Abstract: The epidemic of COVID‐19 appears to be reshaping the world, separating before and after, present and past. Its perceived novelty raises the question of what role the past might play in the present epidemic and in responses to it. Taking the view that the past has not passed, but is present in is material and immaterial remains, and continuously emerging from these, we argue that it should not be studied as closed narration but through the array of its traces, which constitute the texture of the present. To that end, and building on long‐term ethnographic research on past and present epidemics in western Kenya, we assemble here some preliminary observations on the first weeks of COVID‐19 in Kenya. We explore how the acute epidemic crisis currently unfolding is intertwined with layered fragments of earlier epidemic events, attending to material infrastructures, institutional practices, and ritual responses, to the presence of virally loaded bodies, pharmaceuticals, and their residues, and to the resurgence of often painful memories and emotions. People in this region have experienced a long century of epidemics and anti‐epidemic measures of varying duration and intensity, from colonial and postcolonial sleeping sickness and smallpox to HIV/AIDS and more recently cancer, alongside actual or anticipated outbreaks of cholera and Ebola. This local perception of one long epidemic qualifies the notion of a radical temporal break that the COVID‐19 pandemic is often associated with in European conversations.